Clinical outcomes of operative arthroscopy and temporomandibular medical infiltration with platelet-rich fibrin in upper and lower articular space (2021)
This study aims to describe the short-term therapeutic results of patients treated with operative arthroscopy and medical infiltration with platelet-rich fibrin in upper and lower articular space. The study design is descriptive observational with retrospective case series of patients with Wilkes II and III. These patients were managed with operative arthroscopy viscosupplementation with platelet-rich fibrin (PRF) and were followed up for up to 8 months to evaluate their response to treatment. 17 patients were included in the study. In the pre-surgical assessment (T1) mean VAS was 7.1 and MID was 22.2 mm. Eight months later (T4) a relevant improvement in both mentioned variables MID 38.2 ± 4.1 and VAS 1.1 ± 0.2 was observed. Regarding the reduction of pain, a significant improvement in symptoms were found, this being 84.6% ± 3.5% and in mandibular mobility satisfactory results were also obtained, improving in 41.7% ± 20.9%. Within the limitations of the study temporomandibular joint arthroscopy and medical infiltration platelet-rich fibrin viscosupplementation is a procedure of limited invasiveness that shows promising results.